Disruption of the Golgi Apparatus and Contribution of the Endoplasmic Reticulum to the SARS-CoV-2 Replication Complex - Hackstadt, Ted; Chiramel, Abhilash I.; Hoyt, Forrest H.; Williamson, Brandi N.; Dooley, Cheryl A.; Beare, Paul A.; de Wit, Emmie; Best, Sonja M.; Fischer, Elizabeth R. (Viruses, 2021)
A variety of immunolabeling procedures for both light and electron microscopy were used to examine the cellular origins of the host membranes supporting the SARS-CoV-2 replication complex. The endoplasmic reticulum has long been implicated as a source of membrane for the coronavirus replication organelle. Using dsRNA as a marker for sites of viral RNA synthesis, we provide additional evidence supporting ER as a prominent source of membrane. In addition, we observed a rapid fragmentation of the Golgi apparatus which is visible by 6 h and complete by 12 h post-infection. Golgi derived lipid appears to be incorporated into the replication organelle although protein markers are dispersed throughout the infected cell. The mechanism of Golgi disruption is undefined, but chemical disruption of the Golgi apparatus by brefeldin A is inhibitory to viral replication. A search for an individual SARS-CoV-2 protein responsible for this activity identified at least five viral proteins, M, S, E, Orf6, and nsp3, that induced Golgi fragmentation when expressed in eukaryotic cells. Each of these proteins, as well as nsp4, also caused visible changes to ER structure as shown by correlative light and electron microscopy (CLEM). Collectively, these results imply that specific disruption of the Golgi apparatus is a critical component of coronavirus replication.